Evaluation of Factors that Influence SKPD Budget Absorption - Satria, Ramadhio; Yentifa, Armel; Rafi, Muhammad (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research analyzes the factors influencing budget absorption in the Solok City SKPD. The approach used is quantitative with a survey method through distributing questionnaires. Data processing in this research used SPSS V.26 from the primary data of 100 respondents. The results of this research, namely the results of the F test, show that budget planning, quality of human resources, budget implementation, and organizational commitment simultaneously significantly affect budget absorption. Based on the results of the partial test using the t-test, budget planning significantly affects budget absorption. In contrast, the quality of human resources, budget execution, and organizational commitment are independent of budget absorption in SKPD Kota Solok.